Establishing Workflows and Opening Access to Data within Natural History Collections. Issue 2 (June 2016) - Orli, Sylvia; Bird, Jessica
The Smithsonian Transcription Center (TC) is a transcription platform for a wide variety of collection items for the Smithsonian museums and units. The National Museum of Natural History (NAANH) collection items present a unique challenge for the TC, as the labels on these items contain a variety of information, requiring a complex transcription template. In addition, the transcribed collection data must be imported back to the NAANH database (EAAu Museum Management System) with prescribed formatting. The Departments of Botany and Entomology at NMNH have worked with the TC through these challenges to create a workflow that addresses these issues while providing high-quality data at a rapid rate. Suggestions for further improvement are examined as well.